A mammalian, glutaminase-free asparaginase enhances venetoclax activity in preclinical AML models with chromosome 7 deletion - Majid, Dhabya; Wang, Zhe; Schalk, Amanda M.; Yuan, Bin; Tatarata, Qi Zhang; Root, Jessica L.; Garza, Araceli Isabella; Yassouf, Mhd Yousuf; Gamal, Basant T.; Feri-Borgogno, Sammy; Nguyen, Annie Hoai; Konopleva, Marina; et al. (Frontiers in Oncology, 2026)
IntroductionAcute myeloid leukemia (AML) remains a malignancy with poor prognosis andfrequent resistance to standard therapies, underscoring the urgent need for novel treatmentstrategies. In this preclinical study, we evaluated the anti-leukemic efficacy of EBD-300, a novelmammalian-derived asparaginase lacking glutaminase activity, in combination with Venetoclax(VEN).ResultsEBD-300 monotherapy exhibited significant activity in AML cell lines harboringchromosome 7/7q deletions, which are likely dependent on extracellular asparagine due to thepresence of only a single copy of the asparagine synthetase (ASNS) gene - the enzymeresponsible for endogenous asparagine synthesis. The combination of EBD-300 with VENdecreased the IC50 values of some VEN-resistant AML cell lines and reduced the colony-formingcapacity of primary AML patient samples. In patient-derived xenograft (PDX) mouse models,EBD-300, alone or in combination with VEN, significantly reduced leukemic burden in theperipheral blood, bone marrow, and spleen, and improved overall survival in one model.DiscussionAlthough survival benefits were observed in some, but not all, models, suggestingpotential model-specific effects, these findings collectively support a potential therapeutic roleEBD-300 in combination with VEN in AML. While weight loss was observed, EBD-300 mayrepresent a potentially safer alternative to conventional bacterial asparaginases by mitigatingthe adverse effects typically associated with the glutaminase coactivity of the bacterialasparaginases, an observation that requires further investigation.